2015
DOI: 10.1007/s10035-015-0559-z
|View full text |Cite
|
Sign up to set email alerts
|

Grain crushing and high-pressure oedometer tests simulated with the discrete element method

Abstract: The present paper investigates the influence of microstructural inhomogeneities of brittle grains on grain crushing in cohesionless, frictional granular materials, using the discrete element method. Macrograins are modelled as assemblies of bonded micrograins of different sizes and bond strengths to simulate crushed sandstone. A method is suggested to incorporate fracture mechanical properties in the model through the selection of bond properties. Normal distribution of bond strengths, as well as degraded bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 42 publications
(84 reference statements)
1
8
0
Order By: Relevance
“…Such a compression behavior was also observed for arbitrary granular materials and it is also verified by numerical simulations with the discrete element method, e.g. [71,72]. Experimental work has shown that the pressure at the point of inflection depends mainly on the mineral composition and the state of weathering of the solid material.…”
Section: Introduction Of the Solid Hardness In The Sense Of A Continusupporting
confidence: 55%
“…Such a compression behavior was also observed for arbitrary granular materials and it is also verified by numerical simulations with the discrete element method, e.g. [71,72]. Experimental work has shown that the pressure at the point of inflection depends mainly on the mineral composition and the state of weathering of the solid material.…”
Section: Introduction Of the Solid Hardness In The Sense Of A Continusupporting
confidence: 55%
“…Cheng et al [22] randomly removed 20% of elementary balls in an agglomerate to provide a statistical variability to the strength of the agglomerates. Laufer [38] investigated high-pressure compression tests on brittle grains and found that the crushing strengths of the grains are directly proportional to the bond strengths, including normal distributed bond strengths, degraded bonds, and uniformly increased/decreased bond strengths. In this study, increased bond strengths of tensile strength (σ c ) and cohesion (c) were set to get the random strength of the agglomerates.…”
Section: Dem Methods For a Sand Samplementioning
confidence: 99%
“…To date, several different approaches have been used to model post-grain failure using PFC (Cil & Alshibli, 2014;Couroyer et al, 2000;Fu et al, 2017;Laufer, 2015;Marketos & Bolton, 2009;Sun et al, 2018;B. Wang et al, 2008).…”
Section: Grain Failure Modelmentioning
confidence: 99%